Social inclusion of children with intellectual disabilities in Accra, Ghana: Views of parents/guardians and teachers - Hervie, V.M. (Children and Youth Services Review, 2023)
Guided by Bronfenbrenner (1979) ecological systems theory, this study examined social inclusion for children with intellectual disabilities from the perspectives of parents, guardians and teachers in Accra, Ghana. The goal of the study was to explore perspectives of parents, guardians, and teachers regarding social inclusion for children with intellectual disabilities in Ghanaian society. The objectives were to explore (a) beliefs about intellectual disabilities among parents/guardians and teachers in selected schools in the Greater Accra region of Ghana (b) challenges encountered by parents/guardians of children with intellectual disabilities in Accra, Ghana and (c) benefits of special education for children with intellectual disabilities in Accra, Ghana. A descriptive study design with qualitative data collection and purposive sampling methods were utilised to recruit 17 participants for the study. This consisted of eight parents and guardians who have children with intellectual disabilities and nine teachers who teach these children. Data were collected using individual in-depth interviews and observation of participants and analyzed thematically. The findings indicated that children with intellectual disabilities encountered challenges related to beliefs about intellectual disabilities, parental neglect, financial difficulties and labelling and stigma. Furthermore, evidence showed that children with intellectual disabilities benefited from special education in terms of improved communication, bonding with teachers and peers and skill acquisition to deal with challenges they face. Based on the findings of the study, conclusions and implications are discussed for social work practice and policy.
Research Article
Keywords: Beliefs; Children; Ghana; Intellectual disability; And social inclusion